2022
DOI: 10.1038/s41467-022-32678-2
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic ozone decomposition and adsorptive VOCs removal in bimetallic metal-organic frameworks

Abstract: Atmospheric ozone has long been a threat to human health, however, rational design of high-performance O3-decomposition catalysts remains challenging. Herein, we demonstrate the great potential of a series of isomorphous bimetallic MOFs denoted as PCN-250(Fe2M) (M = Co2+, Ni2+, Mn2+) in catalytic O3 decomposition. Particularly, PCN-250(Fe2Co) showed 100% O3 removal efficiency for a continuous air flow containing 1 ppm O3 over a wide humidity range (0 ‒ 80% RH) at room temperature. Mechanism studies suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 63 publications
2
58
0
Order By: Relevance
“…Moreover, the CuÀ NÀ C/GC carries a much better ORR activity compared to the samples prepared from single support of CuÀ NÀ C/CNTs and CuÀ NÀ C/rGO (Figure S12), testifying the 3D structures composed of CNTs and graphene nanosheets and high-content Cu SAS could benefit to mass and electron transfer during the electrochemical process. [38][39][40][41] As illustrated in Figure S13 and Table S6, CuÀ NÀ C/GC displays the lowest Tafel slope of 64.9 mV dec À 1 , implying a fast kinetics towards ORR. Compared to the Cu SAS catalysts derived from different…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the CuÀ NÀ C/GC carries a much better ORR activity compared to the samples prepared from single support of CuÀ NÀ C/CNTs and CuÀ NÀ C/rGO (Figure S12), testifying the 3D structures composed of CNTs and graphene nanosheets and high-content Cu SAS could benefit to mass and electron transfer during the electrochemical process. [38][39][40][41] As illustrated in Figure S13 and Table S6, CuÀ NÀ C/GC displays the lowest Tafel slope of 64.9 mV dec À 1 , implying a fast kinetics towards ORR. Compared to the Cu SAS catalysts derived from different…”
Section: Resultsmentioning
confidence: 97%
“…Zang and co-workers prepared a manganese-based MOF, ZZU-281, which exhibited exceptionally high catalytic activity for O 3 decomposition over the entire humidity range . Recently, we demonstrated that a bimetallic MOF, PCN-250­(Fe 2 Co), could not only catalytically decompose O 3 but also adsorptively remove various VOCs from ambient air effectively, which are not only a class of hazardous air pollutants but also the precursor of O 3 . These works revealed that the catalytically active centers of MOFs for O 3 decomposition were their metal centers, and only some redox-active metal centers (Fe, Mn, and Co) could show high catalytic activity.…”
Section: Introductionmentioning
confidence: 97%
“…The World Health Organization (WHO) updated the Air Quality Guidelines (AQG) level of ambient O 3 concentration to 100 μg m –3 for 8 h of exposure on average in 2021 . O 3 is relatively stable at low concentrations and difficult to spontaneously decompose to O 2 in ambient air . Hence, it is of great significance to study O 3 pollution elimination for the sake of public health and the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the complex and harsh preparation process and expensive raw materials of MOF greatly limited them in mass production and industrial application . In particular, the structure of MOF may be destroyed by exposure to O 3 . , Therefore, it is of great scientific significance and application value to develop a stable water-resistant catalyst with high efficiency and low cost for O 3 elimination.…”
Section: Introductionmentioning
confidence: 99%